In vivo effects of bacterial lipopolysaccharide on proliferation of macrophage colony-forming cells in bone marrow and peripheral lymphoid tissues. - Yokochi, T (1985)
Changes in the number of macrophage colony-forming cells in various tissues of mice injected with lipopolysaccharide (LPS) from Klebsiella pneumoniae, Escherichia coli, or Salmonella enteritidis were studied. The injection of LPS increased macrophage colony-forming cells in peripheral lymphoid tissues such as the spleen, mesenteric lymph nodes, and regional lymph node, although the same treatment caused the decrease of such cells in the bone marrow. This phenomenon was consistently observed when tested by various LPSs. The injection of LPS into mice which had been exposed to X-ray irradiation and reconstituted with syngeneic normal bone marrow cells decreased colony-forming cells in the spleen. The increase of macrophage colony-forming cells in the spleen seemed, therefore, not to be due to migration from the bone marrow. The injection of LPS appeared to shorten the lag time before the initiation of mitosis of colony-forming cells in the spleen but not in the bone marrow. No participation of serum factors in this phenomenon could be detected. It was suggested that there might be an essential difference between the responsiveness to LPS of macrophage colony-forming cells in the spleen and those of the bone marrow.